The Euro System and the Overall European Project: Failure or Fully-Fledged Success? - Pivetti , Massimo (Revista de Economía Crítica, 2024)
Some critical economists appear to believe that the European monetary union (EMU) has gone somewhat astray, and that the working of the euro area could be made significantly better if only the flawed nature of a few key theoretical underpinnings of the project was duly recognized. Quite to the contrary, it is maintained in this article that EMU has indeed been fully successful from the point of view of its actual objective, which has never been that of increasing the overall welfare of the majority of the population concerned. In the light of actual experience, EMU can be interpreted as a deliberate project to undermine wage earners’ bargaining power throughout the Continent. The building of the euro system is shown in the article to have been but the way in which the epoch-making policy shift suffered by advanced capitalism as a whole since the early 1980s was brought about in continental Europe. Differently from the USA and the UK, in continental Europe that shift, with its attack on the material living conditions of wage earners, developed gradually and indirectly through the progressive draining away of national economic sovereignties. It is the removal of the nation state, coupled with the absence of a supranational political power, that the building of the euro system has largely achieved. The preservation and strengthening of this double absence is what the strenuous safeguard of the system is currently aiming at.